“My Grades Are Always Equal to Standardized Critetria” : Discovering EFL Learners’ Motivation Outside Formal Classroom - Siti Jannatussholihah; Ashadi; Erna Andriyanti (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2020)
Motivation in language mastery is a crucial aspect that supports learner success especially in non-formal education. This study explores the motivation of English language learners in non-formal education as well as their perceived difficulties. Employing a qualitative approach with in-depth-interviews in the data collection, the study involved eight learners from a language course institution in Yogyakarta. The transcribed data were analyzed, interpreted, and categorised based on types of motivation and difficulties. The results show that most of the English learners possess instrumental motivation in learning foreign languages, but some tend to have integrative motivation. The instrumental motivation is mainly linked to efforts to pass the exam or tests with good grades. Their integrative motivation is related to recognizing the culture of the target language speech community and desire to communicate with the target community. Despite their motivation, they faced some difficulties related to language skills, especially reading and listening. In addition, they perceived vocabulary as hindrance in all the four skills. Further research to overcome the difficulties is recommended to maximize the learning achievement.